Associations of serum potassium levels with mortality in chronic heart failure patients - Aldahl, Mette; Jensen, Anne-Sofie Caroline; Davidsen, Line; Eriksen, Matilde Alida; Møller Hansen, Steen; Nielsen, Berit Jamie; Krogager, Maria Lukács; Køber, Lars; Torp-Pedersen, Christian; Søgaard, Peter (European heart journal, 2017)
Medication prescribed to patients suffering from chronic heart failure carries an increased risk of impaired potassium homeostasis. We examined the relation between different levels of serum potassium and mortality among patients with chronic heart failure. From Danish National registries, we identified 19 549 patients with a chronic heart failure diagnosis who had a measurement of potassium within minimum 90 days after initiated medical treatment with loop diuretics and angiotensin converting enzyme inhibitors or angiotensin-II receptor blockers. All-cause mortality was examined according to eight predefined potassium levels: 2.8-3.4 mmol/L, 3.5-3.8 mmol/L, 3.9-4.1 mmol/L, 4.2-4.4 mmol/L, 4.5-4.7 mmol/L, 4.8-5.0 mmol/L, 5.1-5.5 mmol/L, and 5.6-7.4 mmol/L. Follow-up was 90 days from potassium measurement. We estimated the risk of all-cause mortality using multivariable adjusted Cox proportional hazard model, with normal serum potassium level at 4.2-4.4 mmol/L as reference. After 90 days, the mortality in the eight strata was 14.4, 8.0, 6.3, 5.0, 5.8, 7.9, 10.3, and 21.1% respectively. In multivariable adjusted analysis, patients with potassium levels of 2.8-3.4 mmol/L [hazard ratio (HR): 3.16; confidence interval (CI): 2.43-4.11], 3.5-3.8 mmol/L (HR: 1.62; CI: 1.31-1.99), 3.9-4.1 mmol/L (HR: 1.29; CI: 1.08-1.55), 4.8-5.0 mmol/L (HR: 1.34; CI: 1.10-1.63), 5.1-5.5 mmol/L (HR: 1.60; CI: 1.29-1.97), and 5.6-7.4 mmol/L (HR: 3.31; CI: 2.61-4.20) had an increased risk of all-cause mortality. Levels within the lower and upper levels of the normal serum potassium range (3.5-4.1 mmol/L and 4.8-5.0 mmol/L, respectively) were associated with a significant increased short-term risk of death in chronic heart failure patients. Likewise, potassium below 3.5 mmol/L and above 5.0 mmol/L was also associated with increased mortality.